Comparison of Aesthetic Perception of Smile Between Dentists and General Population - Hasan Afaq Zaidi; Fazal ur Rehman; Shahbaz Ahmed Jat (Journal of the Dow University of Health Sciences, 2015)
Objective: To compare aesthetic perception of smile between gernal population and dentists by varying lengths of maxillary lateral incisors. Introduction: Patient perception and expectation of their smile plays a very important role when providing an anterior tooth restoration. The aim of conducting the study was to compare the perception of esthetic smile between general population and dentists by varying length of maxillary lateral incisors.